The Stagnation of Indian Exports, 1951-1961 - Cohen, Benjamin I. (Quarterly Journal of Economics, 1964)
Introduction, 604. —I. India's loss in expanding world markets, 606. — II. Empirical evidence that this declining market share was caused by an increase in the price of Indian exports relative to competitors' prices, 608. — III. Policies adopted by the Indian government to achieve goals with higher priority than export promotion, 611. — IV. Policy implications of the historical analysis if the Indian government should adopt a more vigorous export promotion policy, 617. —Appendix, 619.